Vrednost varnosti stavb - Yau, Yung (Urbani izziv, 2015)
Theoretical and empirical studies on how building performance is valued by theproperty market abound in the literature. Some of them investigate changes in property prices after building renovation, but little has been done on pricing the safety performance of buildings. This article presents a study that explores whether residential properties in safer buildings command highermarket values in Hong Kong. Hong Kong is a good laboratory for this study because building failures can pose a serious threat in such a densely populated high-rise environment. The study measures the safety performance of a building by the weighted number of unauthorised building works (UBWs) on theexternal walls of the buildings. By their nature, UBWs are building works that are constructed without prior approval and consent from the government. Ahedonic price model is developed to assess the market value of building safety. For the model estimation, apart from the property transaction data, the number of unauthorised appendages (i.e., UBWs attached to the building facades) in each building studied is obtained through a building survey. Basedon the analysis results, several hypotheses built upon the theories of self-protection and self-insurance are tested.
Keywords: gradbena dela; Hongkong; nadzor; nepremičnine; security; varnost; zgradbe